What is needed for continuity of care and how can we achieve it? - Perceptions among multiprofessionals on the chronic care trajectory - Linda Ljungholm; Anette Edin-Liljegren; Mirjam Ekstedt; Charlotte Klinga (BMC, 2022)
Abstract Background Continuity of care (CoC) implies delivery of services in a coherent, logical and timely fashion. Continuity is conceptualized as multidimensional, encompassing three specific domains - relational, management and informational continuity - with emphasis placed on their interrelations, i.e., how they affect and are affected by each other. This study sought to investigate professionals' perceptions of the prerequisites of CoC within and between organizations and how CoC can be realized for people with complex care needs. Methods This study had a qualitative design using individual, paired and focus group interviews with a purposeful sample of professionals involved in the chain of care for patients with chronic conditions across healthcare and social care services from three different geographical areas in Sweden, covering both urban and rural areas. Transcripts from interviews with 34 informants were analysed using conventional content analysis. Results CoC was found to be dependent on professional and cross-disciplinary cooperation at the micro, meso and macro system levels. Continuity is dependent on long-term and person-centred relationships (micro level), dynamic stability in organizational structures (meso level) and joint responsibility for cohesive care and enabling of uniform solutions for knowledge and information exchange (macro level). Conclusions Achieving CoC that creates coherent and long-term person-centred care requires knowledge- and information-sharing that transcends disciplinary and organizational boundaries. Collaborative accountability is needed both horizontally and vertically across micro, meso and macro system levels, rather than a focus on personal responsibility and relationships at the micro level.